THE ROLE OF RESOLVING DISPUTES RELATED TO INTELLECTUAL PROPERTY OBJECTS THROUGH COURTS AND FOREIGN EXPERIENCE IN THIS AREA (Scientific journal of the Fergana State University, 2024)
The article examines the handling of disputes related to the protection of intellectual property objects in courts, the practical problems encountered in dealing with such cases, and foreign experience in this area. Given that the field of intellectual property rights protection is relatively new and rapidly developing, it is noted that the number of such cases in courts has been increasing annually, with these disputes being heard simultaneously in administrative, criminal, civil, and economic courts. Additionally, the article discusses specialized intellectual property courts in foreign countries and Uzbekistan’s position in international rankings regarding the protection of intellectual property rights. Based on the experience of advanced foreign states, relevant recommendations for improving this field are provided.